Protein Supplementation to Augment the Effects of High Intensity Resistance Training in Untrained Middle-Aged Males: The Randomized Controlled PUSH Trial. (1st June 2017) - Wittke, Andreas; von Stengel, Simon; Hettchen, Michael; Fröhlich, Michael; Giessing, Jürgen; Lell, Michael; Scharf, Michael; Bebenek, Michael; Kohl, Matthias; Kemmler, Wolfgang
Abstract : High intensity (resistance exercise) training (HIT) defined as a "single set resistance exercise to muscular failure" is an efficient exercise method that allows people with low time budgets to realize an adequate training stimulus. Although there is an ongoing discussion, recent meta-analysis suggests the significant superiority of multiple set (MST) methods for body composition and strength parameters. The aim of this study is to determine whether additional protein supplementation may increase the effect of a HIT-protocol on body composition and strength to an equal MST-level. One hundred and twenty untrained males 30–50 years old were randomly allocated to three groups: (a) HIT, (b) HIT and protein supplementation (HIT&P), and (c) waiting-control (CG) and (after cross-over) high volume/high-intensity-training (HVHIT). HIT was defined as "single set to failure protocol" while HVHIT consistently applied two equal sets. Protein supplementation provided an overall intake of 1.5–1.7 g/kg/d/body mass. Primary study endpoint was lean body mass (LBM). LBM significantly improved in all exercise groups (p ≤ 0.043 ); however only HIT&P and HVHIT differ significantly from control (p ≤ 0.002 ). HIT diverges significantly from HIT&P (p = 0.017 ) and nonsignificantly from HVHIT (p = 0.059 ), while no differences were observed for HIT&P versus HVHIT (p = 0.691 ). In conclusion, moderate to high protein supplementation significantly increases the effects of a HIT-protocol on LBM in middle-aged untrained males.